Impact of firm characteristics, macroeconomic conditions, bank regulation and supervision on social and financial efficiency of microfinance institutions - Zainal, Nurazilah (2019)
Commercial banks have witnessed the failure of poverty reduction due to high risk to serve for poor people. Microfinance institutions (MFIs) were established to fill the gap created by the commercial banks by providing a financial service mainly for low income people. In the drive to supply continuous financial services for the poor, performance of the MFIs has been one of the crucial aspects needs to consider. The MFIs begins the operation with its social goal aims for poverty reduction. However, the commercialization of Microfinance in the 1990s has resulted them to become a financial independent, since they are fully funded by a government in previous. Thus, to count solely on the social goal to measure the performance of the MFIs is no longer consistent. They need to be in parallel with the financial goal to ensure the stability of the MFIs in providing financial products in the long run. The commercialization also has upgraded the legal status of the MFIs to be regulated and govern by bank regulation and supervision. Is it acceptable for the MFIs with dual needs of social and financial sustainability being govern under the same roof with the commercial banks? To date, the question is remained debatable. This study proposes to determine the performance of the MFIs from two different aspects of social and financial efficiency in the first objective. In the second objective is to examine the impact of firm characteristics and macroeconomic conditions on the level of social and financial efficiency of the MFIs. The third objective of the study is to investigate the effect of bank regulation and supervision on social and financial efficiency of the MFIs. The data consists of 168 MFIs from five countries in Southeast Asia region (ASEAN-5) from 2011 until 2017. First stage of analysis is to identify the level of social and financial efficiency of the MFIs by using Data Envelopment Analysis (DEA) method. The data are further tested by parametric (t-test) and non-parametric Mann-Whitney (Wilcoxon) and Kruskal-Wallis tests. Second stage of analysis is to evaluate the determinants and the impact of bank regulation and supervision on the social and financial efficiency by applying the Multivariate Panel Regression Analysis (MPRA) and Generalized Method of Moments (GMM) as an estimation method. The findings in the first stage analysis show the score of financial efficiency is higher than social efficiency. Although the MFIs is financially efficient to sustain the operation in the long run, the result also discovers the MFIs in ASEAN 5 countries are inconsistent to balance between the social and financial performance as they tend to focus more in achieving financial sustainability thus leave the social effort for poverty eradication. In the second stage of analysis, main result from the GMM estimations indicates the firm characteristics and macroeconomic conditions give a significant influence on the social and financial efficiency of the MFIs. Furthermore, the results also present the significant impact of bank regulation and supervision to the social and financial efficiency of MFIs. However, bank regulation and supervision are found to give more positive impacts to the financial efficiency while negatively effect to the social efficiency of the MFIs. This indicates the bank regulation and supervision are not appropriate with operations of the MFIs since they are not equally fulfill between the social and financial needs of the MFIs. Overall, the study provides a new insight to the MFIs industry especially for the bank regulators and policy makers to develop a uniform set of regulation and supervision that more appropriate with the nature of the MFIs operations. This is to ensure the MFIs able to achieve financial goal for sustainability in the long run while in the same time accomplish the social goal for poverty reduction.